IMPLEMENTASI MEDIA SUITCASE EMOJI UNTUK MENINGKATKAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI RAUDLATUL ATHFAL AL-JAZIEL PAMEKASAN - Anis Rahmawati; Musayyadah Musayyadah (Dewan Pendidikan Pamekasan, 2023)
Early childhood education is a comprehensive development process for children from birth to six years of age, which includes physical and non-physical aspects, by providing appropriate and correct stimulation for physical, moral, spiritual, motor, emotional, cognitive and social development so that children can grow and develop optimally. Playing is very beneficial for early childhood. Through playing activities, children can learn and learn many things, can recognize rules, socialize, position themselves, manage emotions, tolerance, and good cooperation. Based on the results of research that the author did in class B (equivalent to the age of 5-6 years) at RA Al-Jaziel Jarin Pademawu Pamekasan on April 12, 2022, it is known that the social-emotional development of children has not developed optimally. The purpose of this study was to determine the implementation of Suitcase Emoji media to improve the social-emotional development of children aged 5-6 years at RA Al-Jaziel. This research uses descriptive qualitative with research subjects are students and teachers. Data were collected through observation, interviews, and documentation. The data were analyzed qualitatively using reduction, data presentation, and conclusion drawing. The importance of using good and appropriate media according to the needs of children can improve all aspects of development, one of which is social-emotional development. The impact of this media suitcase emoji is that it can help children in controlling themselves, including the habit of queuing during the Koran, and being disciplined when entering class. And prosocial behavior, among others, children can play with their peers, willing to share with friends. And can be helpful to his friends.